Natural Resources and the Poor : Introduction to a Special Issue of the Journal of Natural Resources Policy Research - Heltberg, Rasmus (Taylor and Francis, 2013)
Natural resources, unless of commercial interest, are hardly a prominent concern of most policy-makers. A certain complacency seems to prevail in which too little is done to increase the productivity and sustainability of the natural resource base on which the rural poor continue to rely for low-productivity semi-subsistence livelihoods. Natural resources remain integral to the livelihoods of billions in developing countries, providing food, fuels, water, biodiversity, raw materials, spiritual fulfillment, and more; they are also vital for the development prospects of many countries. It is therefore surprising that not more attention is paid to them. The status quo is not sustainable. Traditional low-productivity natural resource-based livelihoods do not lift people out of poverty; such livelihoods offer little more than a precarious subsistence survival at the margins of the global economy.The five new research papers in this special issue describe an uneasy and sometimes unhealthy co-existence between natural resources and the poor.